A chegada do Espiritismo no Brasil e sua influência nos rituais afro-brasileiros – a ascensão do “Baixo Espiritismo” (1900-1950) (Revista Sapiência: sociedade, saberes e práticas educacionais (2238-3565), 2017)
The late nineteenth and early twentieth centuries would be marked by a deep movement in Afro-Brazilian religions. The numerous religious practices and rituals in formation in Bahia and Rio de Janeiro would receive the influence of the newly arrived French Spiritism, marked by the foundation of the Brazilian Spiritist Federation (FEB) in 1884. The influence of this religion on the rituals of "macumbas" and candomblés would lead to the formation of a new religious movement, classified at that time as "low spiritism", a pejorative term that served to differentiate the spiritist practices that were mixed with the Afro-Brazilian rituals of orthodox spiritualism , which followed the books of Allan Kardec. In this research we analyze the transformations in this period occurred from the cultural contacts between these religions, that would later lead to the Umbanda religion organization.